2011
DOI: 10.3171/2011.5.peds1140
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic mechanisms regulating neural development and pediatric brain tumor formation

Abstract: Pediatric brain tumors are the leading cause of cancer-related death in children, and among them, embryonal tumors represent the largest group with an associated poor prognosis and long-term morbidity for survivors. The field of cancer epigenetics has emerged recently as an important area of investigation and causation of a variety of neoplasms, and is defined as alterations in gene expression without changes in DNA sequence. The best studied epigenetic modifications are DNA methylation, histone modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 156 publications
(136 reference statements)
1
25
0
Order By: Relevance
“…DNA methylation is an increasingly important tool when it comes to tumor classification [19] and has been shown to play an important role in pediatric brain tumors [22]. Previous studies have shown that tumors, briefly cultured primary cells and cell lines have different methylation profiles and cluster separately [23, 24].…”
Section: Resultsmentioning
confidence: 99%
“…DNA methylation is an increasingly important tool when it comes to tumor classification [19] and has been shown to play an important role in pediatric brain tumors [22]. Previous studies have shown that tumors, briefly cultured primary cells and cell lines have different methylation profiles and cluster separately [23, 24].…”
Section: Resultsmentioning
confidence: 99%
“…Epigenetics refer to studies of mitotically heritable modifications in gene expression that do not involve changes in DNA sequence, presenting a link between genotype and phenotype. In DNA replication the paternal epigenetic information is translated by enzymes known as "readers" which lead to the recruitment of other proteins termed as "writers", or "erasers" and preserve this information in the daughter strands (10). The main epigenetic mechanisms are DNA methylation, histone modifications and small noncoding RNAs (miRNAs).…”
Section: Epigenetic Mechanisms In Tumor Developmentmentioning
confidence: 99%
“…CpG nucleotides are frequently found at the 5' end of the gene promoter and/or the first exon region as big clusters, termed CpG islands (8). The CpG nucleotides inside CpG islands are usually unmethylated, but more than 80% of those traced outside of CpG islands are commonly found methylated (10). DNA methyltransferases (DNMTs) are catalyzing the reaction of methylation and can be distinguished into two subgroups: maintenance methylation and de novo methylation (10).…”
Section: Epigenetic Mechanisms In Tumor Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The H3K27me3 modification regulates the expression of genes associated with lineage commitment, cellular differentiation, and anterior-posterior patterning (Faria et al 2011;Grossniklaus and Paro 2014). Thus, H3K27 has a role in normal brain development.…”
mentioning
confidence: 99%